Bent Bragg–Laue monochromator for high‐energy X‐rays. Issue 4 (26th July 2017) - Shi, Xianbo; Xu, Wenqian; Yakovenko, Andrey; Halder, Gregory; Liu, Zunping; Kurtz, Charles; Ribaud, Lynn; Beyer, Kevin; Chapman, Karena; Chupas, Peter
Abstract : A double‐crystal monochromator composed of a meridionally bent Bragg crystal and a sagittally bent Laue crystal is proposed for bi‐directional focusing of high‐energy X‐ray beams. Abstract : A bent Bragg–Laue monochromator (BLM) is proposed for high‐energy X‐ray (∼25–60 keV) beamlines. The BLM has the unique feature of bi‐directional focusing. A sagittally bent Laue crystal can focus the large horizontal fan of a bending magnet or wiggler source. A meridionally bent Bragg crystal focuses the beam vertically and corrects for the anticlastic bending effects of the Laue crystal. This monochromator geometry relies on the crystal orientations being optimized. It is shown that the focusing condition and Rowland condition can be simultaneously satisfied at a given energy. Detailed ray tracings indicate that a BLM can provide similar energy resolution and higher flux density compared to a sagittally bent double‐Laue monochromator configuration. A prototype BLM with a symmetric Bragg crystal and an asymmetric Laue crystal was tested. Matching of the bend radii of the two crystals in the meridional direction was demonstrated. In general, the horizontal acceptance of the sagittally bent Laue crystal is limited by the large curvature. This horizontal BLM acceptance could be increased by translating the Laue crystal along its sagittal bending axis.